Choosing the Right Test (Influenza) Versus Respiratory Viral Panel With Faster Turnaround Time and Cost Savings. (11th September 2019) - Lin, Bo; Christian, Manan; Kogan, Margarita; Zuretti, Alejandro
Abstract: Introduction: Respiratory infections are very common in hospital patients. Viral pathogens including influenza (Flu) and respiratory syncytial virus (RSV) are frequent causes. Respiratory viral panels (RVPs) have been routinely ordered in our institution with a turnaround time (TAT) of 48 hours at a cost of approximately 170/test. Meanwhile, Flu and RSV PCR are offered in house with a TAT of only 40 minutes and much lower cost (40/test) than RVP. Here, we examined the optimization of use of these tests in our medical center. Methods: Results of the specimens sent for RVP testing as well as their results from Flu/RSV PCR and the negative result rate were reviewed. The TAT and costs were compared between RVP and Flu/RSV PCR. Results: We reviewed 69 specimens from MICU sent for RVP during 10/1/2018 to 1/31/2019. Total negative specimen rate was 74%. The specimens identified positive for Flu or RSV by RVP were also positive for in-house Flu/RSV PCR. Therefore, we have recommended clinicians to order in-house highly sensitive and specific Flu/RSV PCR first for faster TAT and cost saving. Since the recommendation, the number of RVP orders has dropped from 660 (January 2018) to 131 (January 2019), with savings of more than 80, 000 in 1 month. Conclusion: In-house Flu/RSV PCR test is highly sensitive and specific for identifying the common viral pathogens in patients with respiratory infection. It is fast and relatively low cost compared to RVP and should be considered as an effective first-line test.